Discussions About Driving Between Older Adults and Primary Care Providers. Issue 6 (20th June 2016) - Betz, Marian E.; Kanani, Halinganji; Juarez‐Colunga, Elizabeth; Schwartz, Robert
Abstract : Objectives: To estimate how many older adults discuss driving with a primary care provider during a calendar year and to describe discussion triggers. Design: Observational retrospective medical record review. Setting: Three primary care clinics (geriatric, hospital‐based general internal medicine (GIM), community‐based GIM) affiliated with a tertiary care hospital. Participants: Random sample of 240 older (aged ≥65) adults with one or more primary care visits in 2014 (January 1 to December 31). Measurements: Standardized chart abstraction of participant demographic characteristics, medical diagnoses, and presence and context of discussions about driving. Provider factors (obtained from clinic administrators) included sex and average amount worked per week. Results: Participants who visited the geriatric clinic were oldest, had more medical diagnoses, and had a median of 4 visits in 2014 (vs 3 visits in GIM clinics). Documented discussions about driving occurred with a greater proportion of participants in the geriatric (n = 22, 28%, 95% confidence interval (CI) = 18–39%) and GIM hospital (n = 15, 19%, 95% CI = 11–29%) clinics than the GIM community clinic (n = 6, 7.5%, 95% CI = 2.8–16%). Medical diagnoses that might affect driving were prevalent but not associated with frequency of documented discussions. In multivariable analysis, participants were more likely to have one or more documented driving discussions in 2014 if they went to the geriatric clinic or had a primary care provider younger than 45 or who worked fewer than six half‐day clinics per week. Conclusion: Over 1 year, a minority of older adults had a documented discussion about driving with a primary care provider, with differences according to clinic and provider characteristics. Strategies to support routine and preparatory conversations about driving should incorporate these findings and might vary among clinic settings.